Evaluation of the effects of processing delays and protective plastic cases on image quality of a photostimulable phosphor plate system - Clóvis Monteiro Bramante; Alexandre Silva Bramante; Rogério Emílio de Souza; Ivaldo Gomes Moraes; Norberti Bernardineli; Roberto Brandão Garcia (University of São Paulo, 2008)
This ex vivo study evaluated the quality of digital radiographic images obtained with the photostimulable phosphor plate system (Digora) according to the processing delay and maintenance of optical plates in either opaque (supplied with the system) or transparent protective plastic cases during this period. Five radiographs were obtained from the mandibular molar region of a dry human mandible using optical plates. These plates were placed in the protective plastic cases before obtaining the radiographs and were processed immediately or after processing delays of 5, 60 and 120 min, when the case was removed. The results revealed a reduction in image quality when processing was delay 120 min compared to the other times. The opaque case provided better protection to the sensor than the transparent case. In conclusion, a 120-min processing delay for the Digora system caused a reduction in image quality, yet without interfering with the quality of diagnosis. The opaque case supplied by the system's manufacturer provided better protection to the optical plate than the transparent case.